Characterization of Retinal Structure in ATF6 -Associated Achromatopsia - Mastey, Rebecca R.; Georgiou, Michalis; Langlo, Christopher S.; Kalitzeos, Angelos; Patterson, Emily J.; Kane, Thomas; Singh, Navjit; Vincent, Ajoy; Moore, Anthony T.; Tsang, Stephen H.; Lin, Jonathan H.; Young, Marielle P.; et al. (Investigative ophthalmology & visual science, 2019)
Mutations in six genes have been associated with achromatopsia (ACHM): CNGA3, CNGB3, PDE6H, PDE6C, GNAT2, and ATF6. ATF6 is the most recent gene to be identified, though thorough phenotyping of this genetic subtype is lacking. Here, we sought to test the hypothesis that ATF6-associated ACHM is a structurally distinct form of congenital ACHM. Seven genetically confirmed subjects from five nonconsanguineous families were recruited. Foveal hypoplasia and the integrity of the ellipsoid zone (EZ) band (a.k.a., IS/OS) were graded from optical coherence tomography (OCT) images. Images of the photoreceptor mosaic were acquired using confocal and nonconfocal split-detection adaptive optics scanning light ophthalmoscopy (AOSLO). Parafoveal cone and rod density values were calculated and compared to published normative data as well as data from two subjects harboring CNGA3 or CNGB3 mutations who were recruited for comparative purposes. Additionally, nonconfocal dark-field AOSLO images of the retinal pigment epithelium were obtained, with quantitative analysis performed in one subject with ATF6-ACHM. Foveal hypoplasia was observed in all subjects with ATF6 mutations. Absence of the EZ band within the foveal region (grade 3) or appearance of a hyporeflective zone (grade 4) was seen in all subjects with ATF6 using OCT. There was no evidence of remnant foveal cone structure using confocal AOSLO, although sporadic cone-like structures were seen in nonconfocal split-detection AOSLO. There was a lack of cone structure in the parafovea, in direct contrast to previous reports. Our data demonstrate a near absence of cone structure in subjects harboring ATF6 mutations. This implicates ATF6 as having a major role in cone development and suggests that at least a subset of subjects with ATF6-ACHM have markedly fewer cellular targets for cone-directed gene therapies than do subjects with CNGA3- or CNGB3-ACHM.